The Current Role of Liraglutide in the Pharmacotherapy of Obesity - A. Christou, Georgios; Katsiki, Niki; N. Kiortsis, Dimitrios (Current Vascular Pharmacology, 2016)
Objective: Liraglutide 3.0 mg daily dose is marketed under the brand name Saxenda and was recently approved by both the Food and Drug Administration (FDA) and the European Medicine Agency (EMA) as adjunct to a comprehensive lifestyle intervention to achieve weight loss. Design: Human studies using liraglutide 3.0 mg daily dose were selected through search based on PubMed listings and the Clinical trials.gov database using the term “liraglutide”. Results: During 56 weeks of treatment, liraglutide 3.0 mg treatment resulted in 5.9-8.0% weight reduction, while the placebo-subtracted weight loss was 3.9-6.0%. The proportion of treated patients with ≥ 5% weight loss was 50-76%, while the placebo-subtracted proportion was 29-46%. Liraglutide 3.0 mg treatment also induced a decrease in waist circumference, serum triglycerides, insulin resistance, blood pressure and an increase in high density lipoprotein-cholesterol (HDL-C). The most common side effects were nausea, hypoglycemia, diarrhea, constipation, vomiting and headache. In the majority of patients liraglutide 3.0 mg was well tolerated. Conclusion: Liraglutide 3.0 mg appears to be an effective adjunct to a comprehensive lifestyle intervention to achieve weight reduction and treat obesity-related comorbidities.
Keywords: Liraglutide